The Corsican caper : a novel - Mayle, Peter (Knopf, 2014)
"The beloved author at his effervescent best: his master sleuth, Sam Levitt, eating, drinking, and romancing his way through the South of France-even as he investigates a case of deadly intrigue among the Riviera's jet set. Billionaire Francis Reboul is taking in the view at his coastal estate, awaiting the arrival of vacationing friends Sam Levitt and Elena Morales, when he spies a massive yacht whose passengers seem a little too interested in his property. The yacht belongs to rapacious, unscrupulous Russian tycoon Oleg Vronsky, who's decided he'll stop at nothing to obtain Reboul's villa. And when Reboul refuses to sell, Vronsky's methods quickly turn unsavory. Now, it's up to Sam-he's saved Reboul's neck before-to negotiate with an underworld of mercenaries and hitmen, not to mention the Corsican mafia, to prevent his friend from becoming a victim of Vronsky's "Russian diplomacy." Brimming with head-turning twists, sparkling scenery, and mouthwatering gustatory interludes as only Peter Mayle can write them, The Corsican Caper is a one-way ticket to pleasure, Provence style"--